2003
DOI: 10.1023/a:1024865725713
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Assisted hatching increases the pregnancy, implantation, and ongoing pregnancy rates significantly in patients with a poor prognosis undergoing IVF or ICSI, particularly those with repeated failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(7 citation statements)
references
References 20 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…The findings were similar to those of Edirisinghe et al [19], but were in disagreement with two meta-analyses of different methods of AH by Edi-Osagie et al and Sallam et al that showed a positive trend for patients with repeated implantation failure [20][21][22].…”
Section: Discussionsupporting
confidence: 56%
“…The findings were similar to those of Edirisinghe et al [19], but were in disagreement with two meta-analyses of different methods of AH by Edi-Osagie et al and Sallam et al that showed a positive trend for patients with repeated implantation failure [20][21][22].…”
Section: Discussionsupporting
confidence: 56%
“…Since the first-ever use of assisted hatching (AH) by Cohen et al [ 1 ], a variety of AH techniques have been used including zona thinning (ZT) and the opening or complete removal of the zona by chemical, mechanical, enzymatic, and/or laser-based methods [ 2 3 ]. Although many studies have reported an increased pregnancy outcome by facilitating the hatching process of embryos [ 4 5 6 7 8 9 ], some studies have found no effects or insufficient evidence to determine any effect of AH on live birth rates [ 10 11 ]. According to a literature review in 2008 by the American Society for Reproductive Medicine, there was no reason to recommend the routine performance of AH in women undergoing ART [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there have been multiple reports comparing ART outcomes in cycles with and without AH, most have defined poor prognosis as prior failed cycles or based on maternal age rather than looking specifically at FSH concentration. Many such studies support a role for AH in improving clinical pregnancy rates in women who are at least 38 years old or who have had unsuccessful prior ART cycles; several studies have also demonstrated improvements in ongoing/live birth rates in these subpopulations (1922, 36). In contrast, Assemi et al published a study more analogous to ours in its comparison of 154 initial ART cycles all with FSH >=10 IU/L according to whether AH was performed.…”
Section: Discussionmentioning
confidence: 88%
“…Since the publication of those initial reports, multiple approaches to thinning and breaching the zona pelucida have been proposed (11, 17). However, the data supporting the benefit of AH in ART cycles has been variable and contradictory (11, 1925). Much of the data suggesting a benefit of AH has found improvements in cycles following prior IVF failures, cycles treating women at least 38 years of age, or cycles in which embryo quality is poor (11, 14, 26).…”
Section: Introductionmentioning
confidence: 99%